Using lay counsellors to promote community-based voluntary counselling and HIV testing in rural northern Ghana: A baseline survey on community acceptance and stigma - Baiden, F.; Akanlu, G.; Hodgson, A.; Akweongo, P.; Debpuur, C.; Binka, F. (My University, 2007)
Access to voluntary counselling and HIV testing (VCT) remains limited in most parts of Ghana with rural populations being the least served. Services remain facility-based and employ the use of an ever-dwindling number of health workers as counsellors. This study assessed approval for the use of lay counsellors to promote community-based voluntary counselling and testing for HIV and the extent of HIV/AIDS-related stigma in the Kassena-Nankana district of rural northern Ghana. A cross-sectional questionnaire survey was conducted. Logistic regression was used to identify predictors of the tendency to stigmatize people living with HIV/AIDS (PLWHAs). Focus group discussions were held and analytical coding of the data performed. The majority (91.1%) of the 403 respondents indicated a desire to know their HIV status. Most (88.1%) respondents considered locations outside of the health facility as preferred places for VCT. The majority (98.7%) of respondents approved the use of lay counsellors. About a quarter (24%) of respondents believed that it was possible to acquire HIV through sharing a drinking cup with a PLWHA. About half (52.1%) of the respondents considered that a teacher with HIV/AIDS should not be allowed to teach, while 77.2% would not buy vegetables from a PLWHA. Respondents who believed that sharing a drinking cup with a PLWHA could transmit HIV infection (OR 2.50, 95%CI 1.52-4.11) and respondents without formal education (OR 2.94, 95%CI 1.38-6.27) were more likely to stigmatize PLWHAs. In contrast, respondents with knowledge of the availability of antiretroviral (ARV) drugs were less likely to do so (OR 0.40, 95%CI 0.22-0.73). Findings from the thirteen focus group discussions reinforced approval for community-based VCT and lay counsellors but revealed concerns about stigma and confidentiality. In conclusion, community-based VCT and the use of lay counsellors may be acceptable options for promoting access. Interventional studies are required to assess feasibility and cost-effectiveness.